Hypoxic strength training model: benefits for football elite training systems - Samsonova, A. V.; Tsipin, L. L.; Golubev, A. S. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to test and analyze benefits of hypoxic strength training method in KAATSU format for football elite.